Effects of Dynamic and Static Loads on the Concentration of Sodium and Potassium in Murine Skeletal Muscles - Kapilevich L. V. Leonid Vladimirovich; Milovanova K. G. Kseniya Gennadjevna; Sidorenko S. V. Svyatoslav Vladimirovich; Fedorov S. Sergey; Kironenko T. Tatyana; Zakharova A. Anna; Dyakova E. Elena; Orlov S. N. Sergey Nikolaevich (2020, 2020)
Title screen